UTILIZATION OF ARTIFICIAL INTELLIGENCE IN PUBLIC RELATIONS AS A BOUNDARY SPANNING IN E-COMMERCE TYPE OF B2C - Marsheila Gloria (Sociae Polites, 2018)
Business competition in website-based online sales in the shape of e-commerce in Indonesia creates a challenge for e-commerce companies to have the right strategy to increase the customers’ interest so that they will make a purchase transaction through the e-commerce. As one of e-commerce with Busines to Customer (B2C) transactions, Sale Stock (www.salestockindonesia.com) applies the role of public relations as boundary spanning as a strategy to manage corporate communications with customers. The application of this public relations role is carried out by utilizing Artificial Intelligence (AI) named Soraya as a liaison or provider of information formalized through the Information Technology (IT) channel, scanning and monitoring the organization's external environment, protecting organizations, processing information coming from outside the organization, and gathering, channeling, and selecting current data flows and then becoming information analysis. For Sale Stock, utilizing communication and information technology in the role of public relations will bring benefits in the form of ease of companies to communicate with new customers, promote products to new customers and customers. They become a hallmark of e-commerce in creating attractiveness for customers.